?SPECTRAL STUDIES OF BINARY AND TERNARY COMPLEXES OF SOME SULFA-DRUGS (Biological Sciences - PJSIR, 2001)
The complexes of Sulfamethazine(SMZ),Sulfathiazole(STZ)andTolbutamide(TA)withCum) andFe(III)havebeen investigated. The formation of I:I and 1:2species were inferred from electronic spectra and conductivity measure- ments. The bonding sites are the oxygen of sulphonamide group and heterocyclic nitrogen atom of aryl moiety. Interaction of Cu(lI) and Fe(III) ions with salysaldehyde as the primary ligand and with SMZ, STZ and TA as secondary ligands hasbeenstudied spectrophotometrically.The dataindicatethe formationofternarycomplexes with stoichiometric ratio of (1:I:I). Stabilityofbinary andternary complexeswas foundtobe intheorder. SMZ>STZ>TA